Structural modifications to pregnane neurosteroids alter inhibition of LPS/Lipid A binding at the MD-2 activation site within the TLR4 signaling complex - Lopez, Alejandro G.; Chirasani, Venkat R.; Balan, Irina; Morrow, A. Leslie (Frontiers in Immunology, 2025)
Neurosteroids have emerged as promising candidates for treatment for neuroinflammatory diseases, distinct from their classical GABAergic effects. We previously demonstrated that 3α,5α-THP inhibits binding of the Lipid A moiety of lipopolysaccharide to the Toll-like receptor 4 (TLR4): Myeloid Differentiation factor 2 (MD-2) protein complex with nanomolar affinity, suggesting that this mechanism may underlie its ability to inhibit TLR4 signal activation in macrophages and brain. This study investigates the structure activity relationships (SAR) for this action of pregnane neurosteroids, focusing on their interactions with MD-2. Through a combination of molecular docking, surface plasmon resonance, and molecular dynamics simulations, we evaluated how modifications to the A, C, and D rings of neurosteroids influence their interactions with MD-2, including binding affinity, orientation, and conformation. The data reveal that hydrophobic interactions, particularly involving PHE151, may be key to neurosteroid binding to MD-2, and that D ring modification may alter the competitive inhibition of Lipid A binding and subsequent TLR4 activation by pregnane steroids. Furthermore, the prototypical neurosteroids 3α,5α-THP and progesterone demonstrated deeper MD-2 pocket binding and greater MD-2 stabilization, while SGE 516 induced MD-2 flexibility and weaker competitive inhibition compared to 3α,5α-THP. These insights establish a unique structural and mechanistic basis for the immunomodulatory activity of these neurosteroids and offer a novel conceptual framework for future rational design of therapeutics targeting TLR4-mediated neuroinflammation.